2011
DOI: 10.1063/1.3599452
|View full text |Cite
|
Sign up to set email alerts
|

All-boron analogues of aromatic hydrocarbons: B17− and B18−

Abstract: We have investigated the structural and electronic properties of the B(17)(-) and B(18)(-) clusters using photoelectron spectroscopy (PES) and ab initio calculations. The adiabatic electron detachment energies of B(17)(-) and B(18)(-) are measured to be 4.23 ± 0.02 and 3.53 ± 0.05 eV, respectively. Calculated electron detachment energies are compared with experimental data, confirming the presence of one planar C(2v) ((1)A(1)) isomer for B(17)(-) and two nearly isoenergetic quasi-planar C(3v) ((2)A(1)) and C(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
223
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(229 citation statements)
references
References 82 publications
6
223
0
Order By: Relevance
“…In contrast, the Coalescence Kick (CK) method 30 generates initial structures in a dynamical way: the randomly positioned atoms are pushed toward the center of mass step by step until all connected. The CK method is equivalent to setting an upper bound of l 1 and obtaining a more natural distribution of l 1 at the shorter bond length side.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the Coalescence Kick (CK) method 30 generates initial structures in a dynamical way: the randomly positioned atoms are pushed toward the center of mass step by step until all connected. The CK method is equivalent to setting an upper bound of l 1 and obtaining a more natural distribution of l 1 at the shorter bond length side.…”
Section: Methodsmentioning
confidence: 99%
“…Through a joint study of photoelectron spectroscopy and ab initio computation, Boldyrev and Wang confirmed that anionic boron clusters with up to nineteen atoms are planar or quasi-planar [18,19]. And a particularly attractive…”
Section: Planar Boron Clustersmentioning
confidence: 95%
“…The geometric search was performed using Gaussian, with starting configurations generated at random using the coalescence kick method (CK-Search) [21,22]. This method has been employed successfully by many groups to study small clusters.…”
Section: Methodsmentioning
confidence: 99%